2019
DOI: 10.1126/sciadv.aav2437
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DDR2 enhances tumor response to anti–PD-1 immunotherapy

Abstract: In vivo–based functional genomic screen identifies DDR2 as an important determinant of efficacy of anti–PD-1 immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 54 publications
(84 reference statements)
3
98
0
Order By: Relevance
“…Downregulation of DDR2 in A375 human melanoma cells reduced experimental liver metastases in mice (Badiola, Villacé, Basaldua, & Olaso, 2011). In contrast, a recent study showed no effect of DDR2 downregulation on the ability of mouse B16-F10 melanoma cells to colonize lungs in experimental metastasis assays (Tu et al, 2019). However, a previous study demonstrated that inoculation of B16-F10 melanoma cells into DDR2-deficient mice decreased subcutaneous tumor growth and experimental metastases, suggesting that stromal DDR2 plays a role in melanoma malignancy (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Downregulation of DDR2 in A375 human melanoma cells reduced experimental liver metastases in mice (Badiola, Villacé, Basaldua, & Olaso, 2011). In contrast, a recent study showed no effect of DDR2 downregulation on the ability of mouse B16-F10 melanoma cells to colonize lungs in experimental metastasis assays (Tu et al, 2019). However, a previous study demonstrated that inoculation of B16-F10 melanoma cells into DDR2-deficient mice decreased subcutaneous tumor growth and experimental metastases, suggesting that stromal DDR2 plays a role in melanoma malignancy (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Alterations of some top genes in our prediction, such as B2M, JAK1, JAK2, HSP90 , and IFNG , are known to be associated with poor response to anti-PD-1 therapy [7, 33-36]. Several genes that were recently found to be associated with anti-PD-1 response were also identified in the top list of our prediciton, such as KRAS [37], STK11 [38], DDR2 [39], and ATR [40].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several efforts tested possible drug combinations with checkpoint inhibitors. However, tests of all the possible drug combinations with PD-1/PD-L1 inhibitors may exceed the number of eligible cancer patients who can be enrolled in clinical trials, and are therefore not feasible in the context of clinical trials [39]. With the incorporation of drug target information, our approach can be used to effectively identify compounds that may have action in pathways that enhance response to anti-PD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Lizotte et al developed an in vitro luciferase-based screening assay to identify small molecules, which modulate T-cell-mediated killing of tumor cells and validated epidermal growth factor receptor (EGFR) inhibitors at potentiators of anti-PD-1 immunotherapy [193]. Tu et al utilized in vivo functional genomics to identify discoidin domain receptor 2 (DDR2) as a target mechanism to sensitize multiple tumor types to anti-PD-1 treatment [194]. In more encompassing studies, genome-wide CRISPR-Cas9 screens have been leveraged to further elucidate genes, which permit tumor cell escape from immunosurveillance.…”
Section: High-throughput Methods Of Discovering Combinational Therapiesmentioning
confidence: 99%